2011
DOI: 10.1116/1.3610172
|View full text |Cite
|
Sign up to set email alerts
|

Interface stability in stressed solid-phase epitaxial growth

Abstract: The role of applied stress on interface stability during Si solid-phase epitaxial growth was investigated. Transmission electron microscopy observations of growth interface evolution revealed in-plane uniaxial compression ͑tension͒ led to interface instability ͑stability͒. Additionally, level set simulations revealed that the stress-influenced interface instability was accurately modeled by adjusting the strength of the linear dependence of local interface velocity ͑rate of change of interface position with re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 31 publications
(26 reference statements)
0
7
0
Order By: Relevance
“…Morarka et al [101] have argued that the magnitude of the stress concentration is insufficient to account quantitatively for the observations, and have advanced a model in which the applied stress is hypothesized to modify the interfacial tension. They have been able to obtain good agreement with morphologies they observe in multidirectional SPE in device fabrication geometries.…”
Section: Interface Rougheningmentioning
confidence: 99%
“…Morarka et al [101] have argued that the magnitude of the stress concentration is insufficient to account quantitatively for the observations, and have advanced a model in which the applied stress is hypothesized to modify the interfacial tension. They have been able to obtain good agreement with morphologies they observe in multidirectional SPE in device fabrication geometries.…”
Section: Interface Rougheningmentioning
confidence: 99%
“…In principle, for an interface with peaks and trough, variation in the localized stress state should exist due to differences in the elastic properties of amorphous and crystalline Si (Witvrouw and Spaepen, 1993). However, later work showed that variations in the localized stress state, even in the presence of substantial perturbations, were negligible (Morarka et al, 2011). It was thus advanced that a synergistic effect between the applied stress and the localized growth interface curvature was responsible for controlling morphology, though the origin of this is not yet understood.…”
Section: Origins and Driving Forcesmentioning
confidence: 92%
“…If this system is now annealed to effect SPEG, the growth interface will exhibit morphological instability as well as the generation of defects depending on the sign of the applied stress. Specifically, if σ 11 ¼ 0 (stress free) or σ 11 > 0 (tensile), the growth interface will remain flat during SPEG and no defects will be generated, while if σ 11 < 0 (compressive), the growth interface will roughen during SPEG and defects will be generated at the growth interface (Barvosa-Carter et al, 1998, 2004Morarka et al, 2011;Phan et al, 2001;Rudawski et al, 2007Rudawski et al, , 2008bSage et al, 2000;Sklenard et al, 2013). Fig.…”
Section: Externally Stressed Spegmentioning
confidence: 96%
See 2 more Smart Citations